2013
DOI: 10.4136/ambi-agua.1145
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of Salmonella spp. in recreational aquatic environments in the Northeast of Argentina

Abstract: The aim of this work was to detect the presence of Salmonella spp. in recreational aquatic environments in the Northeast of Argentina and to relate it with water and environmental parameters. Sixty eight samples of water from recreational aquatic environments in the provinces of Chaco and Corrientes, Argentina, were studied. Salmonellae were detected in 6 samples (8.8%). Salmonella spp. isolates belonged to the following species and serovars: S. enterica serovar Give, S. enterica subespecie IV, S. enterica ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
0
0
1
Order By: Relevance
“…E. coli isolation in the screened water samples was not in consistent to those found by Selim et al [42], (8.0%) and Barbosa et al [43], (16.5%) also, Momtaz et al [44] , who found that only 4 out of 448 water samples (0.89%) were positive for E. coli. While, our findings for Salmonellae isolates were not matched to those isolated by Yam et al [45], (18.0%), Haley et al [46] (79.2%), Adingra et al [47] (15.4%), Momtaz et al ( [44] (7.58%), Tracogna et al [48] (8.8%), Yhils and Bassey [49] (12.9%) and Abd El-Tawab et al [50] (25.0%). Furthermore, P. aeruginosa was found in 38.9% and A. hydrophila wasn't detected in any of the examined water samples as reported by Mohammed [51].…”
Section: Resultscontrasting
confidence: 85%
“…E. coli isolation in the screened water samples was not in consistent to those found by Selim et al [42], (8.0%) and Barbosa et al [43], (16.5%) also, Momtaz et al [44] , who found that only 4 out of 448 water samples (0.89%) were positive for E. coli. While, our findings for Salmonellae isolates were not matched to those isolated by Yam et al [45], (18.0%), Haley et al [46] (79.2%), Adingra et al [47] (15.4%), Momtaz et al ( [44] (7.58%), Tracogna et al [48] (8.8%), Yhils and Bassey [49] (12.9%) and Abd El-Tawab et al [50] (25.0%). Furthermore, P. aeruginosa was found in 38.9% and A. hydrophila wasn't detected in any of the examined water samples as reported by Mohammed [51].…”
Section: Resultscontrasting
confidence: 85%
“…Generalmente, las sardinas enlatadas se han relacionado con contaminantes no biológicos (22)(23)(24), por lo que este es el primer reporte de contaminación de un producto enlatado por S. Give en el país, lo que se relacionó directamente con su estado de conservación, pues se evidenciaron filtraciones y abolladuras en el empaque y, dado que el lugar de producción no estaba protegido frente a la entrada de contaminantes físicos (aire, agua, polvo) ni biológicos (silvestres y domésticos), es posible inferir que la contaminación de la lata de sardinas por S. Give provenía del contacto directo con alguna especie animal infectada (no identificada), o que actuó como vehículo de contaminación ambiental, lo cual concuerda con la asociación ya establecida de S. Give con animales y ambientes acuáticos (3,4,6,7,(25)(26)(27)(28)(29).…”
Section: Discussionunclassified